Thrombocytopenia and Platelet Dysfunction in Acute Tropical Infectious Diseases - Hapsari Putri, Indri; Tunjungputri, Rahajeng N.; De Groot, Philip G.; van der Ven, Andre J.; de Mast, Quirijn (Seminars in Thrombosis and Hemostasis, 2018)
Thrombocytopenia is a well-known manifestation of acute tropical infectious diseases. The role of platelets in infections has received much attention recently because of their emerging activities in modulation of inflammatory responses, host defense, and vascular integrity. However, while many studies have addressed thrombocytopenia in tropical infections, abnormalities in platelet function have been largely overlooked. This is an important research gap, as platelet dysfunction may contribute to the bleeding tendency that characterizes some tropical infections. The development of novel platelet function assays that can be used in thrombocytopenic conditions (e.g., flow cytometry assays) has contributed to important new insights in recent years. In this review, the importance of platelets in tropical infections is discussed with special emphasis on the underlying mechanisms and consequences of thrombocytopenia and platelet dysfunction in these infections. Special attention is paid to malaria, a disease characterized by microvascular obstruction in which bleeding is rare, and to infections in which bleeding is common, such as dengue, other viral hemorrhagic fevers, and the bacterial infection leptospirosis. Given the importance of platelet function abnormalities in these infections, the development of affordable assays for monitoring of platelet function in low-resource countries, as well as pharmacologic interventions to prevent or reverse platelet function abnormalities, might improve clinical care and the prognosis of these infections.
Keywords: platelets; thrombocytopenia; malaria; dengue; leptospirosis